Revision of the Old World genus Mesocomys Cameron (Hymenoptera: Eupelmidae) - Gibson, Gary A.p. (Zootaxa, 2021)
The Old World genus Mesocomys Cameron (1905) (Hymenoptera: Eupelmidae: Eupelminae) is revised. Eleven species, including two newly described species, are recognized and keyed in two previously established species groups, the albitarsis and the pulchriceps species groups sensu Gibson (1995), but with additional features provided to distinguish members of the two groups. Five species are recognized in the pulchriceps group—Mesocomys anelliformis n. sp., M. longiscapus n. sp., M. orientalis Ferrière, 1935, M. pauliani Ferrière, 1951, and M. pulchriceps Cameron, 1905. Seven species are assigned to the albitarsis group, but one, M. aegeriae Sheng, 1996 is treated as a nomen dubium; the six recognized and keyed species in the albitarsis group are M. albitarsis (Ashmead, 1904), M. breviscapis Yao, Yang & Zhao, 2009, M. menzeli (Ferrière, 1930b), M. obscurus (Ferrière, 1930b) revised stat., M. superansi Yao, Yang & Zhao, 2009, and M. trabalae Yao, Yang & Zhao, 2009. Within the albitarsis group, the species are further discussed relative to two newly established species subgroups, the albitarsis subgroup for M. albitarsis, M. menzeli and M. obscurus, and the aegeriae subgroup for M. aegeriae, M. breviscapis, M. superansi and M. trabalae. Females of the albitarsis subgroup possess a finely sculptured mesoscutal medial lobe in combination with partly infuscate fore wings and/or at least partly pale flagellum, whereas females of the aegeriae subgroup possess a much more coarsely sculptured mesoscutal medial lobe and hyaline fore wings in combination with a dark flagellum. Members of the albitarsis species group are restricted to the Oriental and eastern Palaearctic regions except for a single female of the aegeriae subgroup seen from Algeria that is provisionally identified as M. breviscapis; members of the pulchriceps group are restricted to the Afrotropical region except for M. orientalis from the Oriental region. Newly placed in synonymy are M. aegeriae Sheng, 1998 under M. aegeriae Sheng, 1996 n. syn., M. sinensis Yao, Yang & Zhao, 2009 under M. breviscapis Yao, Yang & Zhao, 2009 n. syn., M. atulyus Narendran, 1995 under M. orientalis Ferrière, 1935 n. syn., M. vuilleti (Crawford, 1912) under M. pulchriceps Cameron, 1905 n. syn., and Semianastatus orientalis Kalina, 1984 and Mesocomys kalinai Özdikmen, 2011 under M. albitarsis (Ashmead, 1904) n. syns. Lectotypes are newly designated for M. menzeli, M. obscurus, M. orientalis, M. pauliani, M. pulchriceps and M. vuilleti. Morphological features characteristic of the genus and of the highly dimorphic sexes are described and illustrated, and the species are keyed, described, and illustrated through macrophotography. Phylogenetics are discussed for the genus, the two species groups, and species within the pulchriceps group. Distribution and host records are also summarized for each species.